Platelet Changes Induced by Elatericin A - Joshua, H; Shohat, B; Cohen, I; Gitter, S (Thrombosis and Haemostasis, 1969)
Elatericin A at a concentration of 3 μg/ml causes spicule formation on platelets and inhibits spreading on glass surfaces, viscous metamorphosis and clot retraction. Elatericin A has no effect whatsoever on the activity of isolated platelet factors. However platelet factor 3-availability is decreased by elatericin A. Platelets treated with elatericin A up to a limiting concentration of 30 μg/ml regain their clot retracting activity if washed and reincubated in normal plasma.Elatericin A does not affect the ATP content nor the ATPase activity of platelets. A normal ADP-release is obtained upon addition of thrombin to elatericin A treated platelets. Addition of ATP and Mg ions does not restore the clot retracting activity of elatericin A treated platelets.